Student Learning Styles in Solving Math Story Problems on the Material of Two-Variable Linear Equation Systems - Ichdar Domu (Journal on Education, 2023)
Students' information gathering is heavily reliant on their learning styles. Mathematical education calls for a deeper examination of methodological variations. This study examines the correlation between students' learning styles and their ability to solve math word problems involving a system of two-variable linear equations. The method employed is a qualitative, descriptive research method. The instruments utilized are student aptitude and learning style assessments. Data analysis methods include data collection, data reduction, and data interpretation. The findings included that the visual and auditory subjects completed only three of the five questions they deemed simple. Comparatively, kinesthetic subjects were able to answer four questions. When reexamining the visual, auditory, and kinesthetic subjects, the obtained answers are not rechecked. By concluding the solution process, visual and kinesthetic subjects exhibit similarities. In the final phase, the auditory subject neither concludes nor responds to the initial questions.